The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1371/journal.pone.0013781
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of Tissue Kallikreins

Abstract: The gene family of human kallikrein-related peptidases (KLKs) encodes proteins with diverse and pleiotropic functions in normal physiology as well as in disease states. Currently, the most widely known KLK is KLK3 or prostate-specific antigen (PSA) that has applications in clinical diagnosis and monitoring of prostate cancer. The KLK gene family encompasses the largest contiguous cluster of serine proteases in humans which is not interrupted by non-KLK genes. This exceptional and unique characteristic of KLKs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
84
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 106 publications
17
84
0
4
Order By: Relevance
“…The human kallikrein 1 (KLK1) protein sequence was used as a query to search the genome of Xenopus tropicalis (frog) in the ENSEMBL database. The hit with the highest score was the sequence ENSXETP00000006440 which, in a previous study (24), was shown to be a bona fide KLK1.…”
Section: Phylogenetic Analysismentioning
confidence: 94%
“…The human kallikrein 1 (KLK1) protein sequence was used as a query to search the genome of Xenopus tropicalis (frog) in the ENSEMBL database. The hit with the highest score was the sequence ENSXETP00000006440 which, in a previous study (24), was shown to be a bona fide KLK1.…”
Section: Phylogenetic Analysismentioning
confidence: 94%
“…[50,53,57,58]. Furthermore, KLKs are encoded by the largest contiguous cluster of proteaseencoding genes in the human genome, and uniquely, they are not interrupted by any other non-KLK genes [49,50,57,59,60].…”
Section: General Overviewmentioning
confidence: 99%
“…KLK gene transcripts code for a single chain serine protease pre-proenzyme of a fixed length, between 248 and 293 amino acids [50,57].…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The KLK locus, which features among the seven highly-ranked susceptibility loci in a multi-stage prostate cancer GWAS , is clustered in a tan dem array of approximately 300 kilobases (kb) on chromosome 19q13.4, and contains the largest cluster of 15 homologous protease genes (Lawrence et al , 2010 ) said to have evolutionarily emerged 330 million years ago (Clements , 2008 ;Pavlopoulou et al , 2010 ). With the recent imperative given to research on the KLK gene locus, many significant gene -disease associations have been established and previously unknown roles of KLK proteins elaborated.…”
Section: Introductionmentioning
confidence: 99%